Linking Purchasing to Ethical Decision-Making: An Empirical Investigation - Husser, Jocelyn (Journal of business ethics, 2014)
The aim of this study is to examine the decision-making processes at work among French buyers—whether beginners or more experienced individuals, when confronted with a dilemma involving an ethical or non-ethical choice to be made. We go on to illustrate these dilemmas through the use of five original scenarios that reproduce typical situations that arise in a purchasing context in relation to the environment, physical integrity, conflict of interest, or paternalism. Based on 172 participants, the results of our study show that, ethical decision-making depends very clearly on two main factors: expertise and gender. The study also reveals that there is not always a coherent link between ethical choices made and the reasons and justifications given for those choices. Ethical options chosen are not exclusively justified on the grounds of purely ethical reasons but also on the grounds of commercial or economic reasons, or else reasons of avoidance.